Two new Indo-Pacific species in the Eviota nigriventris complex (Teleostei: Gobiidae) - Greenfield, David W.; Randall, John E. (Zootaxa, 2011)
Three species are recognized in the Eviota nigriventris complex, two of them new. Eviota nigriventris Giltay is a species with a red ventral band, edged dorsally with a narrow white line, the ventral band ending in an asymmetrical black mark at the caudal-fin base; E. dorsopurpurea n. sp. is a species with a purple back and head and a black ventral band ending in a semi-circular spot; and E. dorsogilva n. sp. is a species with a black to dark reddish ventral band ending in a semicircular spot and has a cream-colored back. Eviota dorsogilva and E. dorsopurpurea also differ in counts, pectoral-fin base coloration and eye size.